Piano Performance And Its PedagogicalSignificance In The Music Education System - Majidova Gulnoza Xasanovna (Euro Asian Journal Publishing, 2025)
This scientific article provides a comprehensive analysis of the role of the piano in the musical education system, its pedagogical and educational significance, as well as the scientific and methodological foundations of teaching piano performance to children and adolescents. The piano serves as a leading tool in the formation of musical literacy not only in professional music performance, but also in general education and specialized music schools. This instrument develops musical hearing, a sense of rhythm, artistic thinking, aesthetic taste, and intellectual abilities in students
Keywords: piano performance; piano; music education